2021
DOI: 10.1590/0103-8478cr20200579
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological characterization of Ceratocystis fimbriata isolates from yerba mate

Abstract: This study aimed to morphologically characterize the isolates of Ceratocystis fimbriata from yerba mate and to evaluate the effect of culture medium and temperature on mycelial growth and sporulation of C. fimbriata. For the morphological characterization of the 11 monosporic isolates of the fungus, slides were prepared to determine the dimensions of the sexual and asexual structures of the fungus. Four experiments were conducted to evaluate the mycelial growth and to evaluate the sporulation of C. fimbriata i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[ 75 , 77 , 78 ], Ficus carica [ 75 , 79 ], Punica granatum [ 80 , 81 ], Colocasia esculenta [ 80 , 82 , 83 ], Theobroma cacao [ 11 ], Gmelina arborea [ 84 , 85 ], Syngonium sp. [ 86 , 87 ] and Ilex paraguariensis [ 88 , 89 ]. In contrast, C. cacaofunesta has only been described in Theobroma cacao [ 90 ] and in species from the genus Herrania sp.…”
Section: Discussionmentioning
confidence: 99%
“…[ 75 , 77 , 78 ], Ficus carica [ 75 , 79 ], Punica granatum [ 80 , 81 ], Colocasia esculenta [ 80 , 82 , 83 ], Theobroma cacao [ 11 ], Gmelina arborea [ 84 , 85 ], Syngonium sp. [ 86 , 87 ] and Ilex paraguariensis [ 88 , 89 ]. In contrast, C. cacaofunesta has only been described in Theobroma cacao [ 90 ] and in species from the genus Herrania sp.…”
Section: Discussionmentioning
confidence: 99%
“…The environment is of great importance in plant diseases. A study showed that the average optimum temperature for mycelial growth and sporulation of isolates of C. fimbriata of yerba mate are around 23°C (Brito et al, 2021). Because the plant growth chamber kept the temperature favourable to the pathogen throughout the experiment, it caused the disease to occur more quickly than in the greenhouse where there was no temperature control and there was great variation during the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was performed in two different environmental conditions. One experiment was carried out in a plant growth chamber (InstalaFrio®) at the Laboratório de Epidemiologia para Manejo Integrado de Doenças, from the Universidade Federal do Paraná Curitiba, PR, Brazil, from October to November 2017, with manual irrigation, temperature of 23 ± 2°C, the optimal for Ceratocystis fimbriata mycelial growth (Brito et al, 2021), relative humidity of 80% and out during the spring season in a greenhouse at the Laboratório de Patologia Florestal of Embrapa Florestas, Colombo, PR, Brazil, from December 2017 to January 2018, without environmental control, which has a 50% shade cloth and manual irrigation. Daily data on temperature (°C) were obtained inside the experiments using maximum and minimum thermometer with a variation of −30 to 50°C (Walmur®).…”
Section: Aggressiveness Of Ceratocystis Fimbriata Isolatesmentioning
confidence: 99%
“…The knowledge of conditions that favours fungal growth and sporulation is important in microbiology and plant pathology. Temperature, relative humidity, and Hydrogen ion concentration are the main players in growth, reproduction and survival of the microorganisms (Brito et al, 2021). Physiological studies on fungi have played an important role in agriculture, industry, medicine and industrial production of vitamins (Madan and Thind, 1998).…”
Section: Introductionmentioning
confidence: 99%